Experimental and numerical evaluation of different powder metallurgical steels for cold forging tools - Falk, Bernd; Engel, Ulf; Geiger, Manfred (Advanced Technology of Plasticity 1999, Proc. of the 6th Int. Conf. on Technology of Plasticity, Vol. 1, 1999)
None
LFT Import::2019-08-05 (1997)